Study on household waste management in Kampung Parit Haji Siraj, Johor, Malaysia - Nazira Binti Azahar, Nazatul; Zuhaili Bin Mohamed Najib, Mohamed; Fikri Bin Basri, Hazlami; Noor Hazwan Jusoh, Muhammad; Noor Hasanah Binti Tuan Ismail, Tuan (Universitas Nahdlatul Ulama Surabaya, 2021)
Waste management issue has been a major threat and challenge due to the undergoing rapid industrialization and urbanization not only to Malaysia, but also other countries around the world. To tackle that, the first step starts at household level where people are encouraged to try to manage their wastes properly. The aim of this study was to review the current practises of household waste management, to assess household awareness of the health and safety risked posed by inadequate handling of special household waste and to identify future prospect and potential for effective waste management system in Kampung Parit Haji Siraj, Ayer Hitam, Johor. A survey questionnaire was used to collect complete information on the objectives stated and the data were analysed using SPSS software. Results showed that 97.2% of residents were aware about waste management and social media with 80% contributed the most in delivering information about waste management to the public. The most type of solid waste generated from household were food waste and plastic with 94.4% and 86.1%, respectively. 66.7% of residents emptied their waste container once in 2 days and about 63.9% of the residents dispose their household waste in a hole near their compound. Majority of the residents are aware of any health and safety risked posed by inadequate handling of household waste. Lastly, waste management system in the area can be improved by providing proper waste disposal place and educating proper disposal ways to guarantee that residents do not discard their waste in an indiscriminate manner.